Bahasa Indonesia Bahasa Indonesia - M Furqon (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of Interactive Conceptual Instruction Assisted by PhET Simulations on students' scientific consistency. The research method used was quasi experiment with the matching-only pretest-posttest control group design involving 62 students in one of the high schools in Indonesia. The instrument used was an scientific consistency test modified from the Representational Variant of Force Concept Inventory (R-FCI). The data obtained were analyzed by t-test and N-Gain. The results showed that Interactive Conceptual Instruction Assisted by PhET Simulations can improve students' scientific consistency.